2013
DOI: 10.1093/bfgp/els059
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the DNA damage response: insights from live-cell imaging

Abstract: All organisms have to safeguard the integrity of their genome to prevent malfunctioning and oncogenic transformation. Sophisticated DNA damage response mechanisms have evolved to detect and repair genomic lesions. With the emergence of live-cell microscopy of individual cells, we now begin to appreciate the complex spatiotemporal kinetics of the DNA damage response and can address the causes and consequences of the heterogeneity in the responses of genetically identical cells. Here, we highlight key discoverie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Further investigation of the components of the DDR pathway is beyond the scope of this study, however it is acknowledged that additional cell cycle and DNA damage biomarkers could be included in subsequent studies to expand our understanding of the mode of action of DDR targeting oncology therapies 43 44 . Studies have been published using live cell imaging and demonstrated that detailed information can be obtained for complex dynamics of intracellular signal transduction pathways 42 , however implementing large mechanistic models, such as those published by Tyson and Novák, would add considerable numbers of model reactions that would require significant experimental resource to parameterize in a relevant cell background 45 46 . Our model was therefore constructed at a resolution corresponding with the experimental data which could be generated within the time-lines relevant to therapeutic drug discovery, and was appropriate to adding mechanistic detail without digressing from the intended functionality of the tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation of the components of the DDR pathway is beyond the scope of this study, however it is acknowledged that additional cell cycle and DNA damage biomarkers could be included in subsequent studies to expand our understanding of the mode of action of DDR targeting oncology therapies 43 44 . Studies have been published using live cell imaging and demonstrated that detailed information can be obtained for complex dynamics of intracellular signal transduction pathways 42 , however implementing large mechanistic models, such as those published by Tyson and Novák, would add considerable numbers of model reactions that would require significant experimental resource to parameterize in a relevant cell background 45 46 . Our model was therefore constructed at a resolution corresponding with the experimental data which could be generated within the time-lines relevant to therapeutic drug discovery, and was appropriate to adding mechanistic detail without digressing from the intended functionality of the tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, detailed studies of single cell dynamics such as the work published by, e.g. the White and Lahav groups, have made substantial contribution to understanding the dynamical behaviors of the interactions within biochemical networks, however it is difficult to translate these complex dynamics into a response in a multi-cellular in vivo tumor model, in order to link mode of action and drug efficacy in a cell population for clinical trial design 41 42 .…”
mentioning
confidence: 99%
“…Experimental induction of DNA damage foci in living cells became an ideal method to analyze in time and space the recruitment and binding properties of repair factors at DNA lesions ( 138 ). Live cell imaging of DNA damage foci has been used to reveal the mobility of repair proteins, their assembly timing into repair sites, and the movement of damaged chromatin ( 139 141 ).…”
Section: Laser Microirradiationmentioning
confidence: 99%
“…Due to the prominent role of positive feedback on ATM, we decided to explicitly consider the generation and repair of DSBs in our model. Recently, we measured DSB dynamics in single cells over time and observed considerable variability in their number and half-life, highlighting the stochastic nature of DSB repair [15,39]. We represent DSB kinetics by a data based modeling approach involving stochastic birth-death processes [40].…”
Section: Atm Kinase Is Involved In a Positive Feedback Driving The P5mentioning
confidence: 99%